PENGARUH PERSISTENSI LABA, GROWTH OPPORTUNITIES, DAN UKURAN PERUSAHAAN TERHADAP RELEVANSI NILAI LABA AKUNTANSI (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI SELAMA PERIODE 2013-2015) - Nia Chanzenia Faradilla; Noor Shodiq Askandar (Universitas Islam Malang, 2017)
This study aimed to test whether (1) the effect of earnings persistence on the value relevance of accounting earnings, (2) growth opportunities on the value relevance of accounting earnings, and (3) the influence of firm size on the value relevance of accounting earnings in manufacturing companies listed on the Indonesia Stock Excange. The population in this study was companies of manufacturing listed on the Indonesia Stock Excange (IDX) in 2013 to 2015. Samples was determined by purposive sampling method and obtain 46 manufacturing companies. The data used in this study are secondary, data obtained from official website www.idx.co.id dan www.yahoofinance.com. Based on the result of the analysis can be put forward several conclusion as follow: (1) the result of F test shows that earnings persistence, growth opportunities, and firm size simultaneosly has no significant effect on value relevance of accounting earnings. (2) the result of t test shows that earnings persistence, growth opportunities, and firm size partialously has no significant effect on value relevance of accounting earnings.